2007
DOI: 10.1002/anie.200701798
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuit of Palau'amine

Abstract: Since its discovery in 1993, the marine natural product palau'amine has intrigued natural product chemists. Its exotic molecular architecture and purported bioactivity made it an ideal target for synthesis. However, as the years went by and related marine alkaloids were isolated, a skeptical eye was cast on the structure of palau'amine; recently these suspicions were confirmed and the structure of palau'amine revised. This Minireview gives a careful overview of the structural revision and its ramifications to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(65 citation statements)
references
References 103 publications
2
62
0
1
Order By: Relevance
“…Although neither X-ray analysis nor total synthesis has yet been possible, the recent isolation of related compounds tetrabromo-styloguanidine (15) and konbuЈacidin B (16) has led to the proposal that 17 is the correct structure of palauЈamine. [66] Compound 17 possesses an unusual and energetically less preferable (calculations: 27.3 kJ mol -1 ) trans-, rather than cis-, five-membered ring fusion. The trans assignment of 15 stems from the predicted size of 3 J 11,12 : 13.1 Hz and 14.6 Hz for the cis-and trans-fused isomers, respectively.…”
Section: Verifying Proposed Structuresmentioning
confidence: 99%
“…Although neither X-ray analysis nor total synthesis has yet been possible, the recent isolation of related compounds tetrabromo-styloguanidine (15) and konbuЈacidin B (16) has led to the proposal that 17 is the correct structure of palauЈamine. [66] Compound 17 possesses an unusual and energetically less preferable (calculations: 27.3 kJ mol -1 ) trans-, rather than cis-, five-membered ring fusion. The trans assignment of 15 stems from the predicted size of 3 J 11,12 : 13.1 Hz and 14.6 Hz for the cis-and trans-fused isomers, respectively.…”
Section: Verifying Proposed Structuresmentioning
confidence: 99%
“…[3][4][5][6] The calculated pK a of 1-H + of +10.9 in aqueous solution indeed suggests that 1 is present quantitatively in its protonated form even under mildly acidic reaction conditions. Protonation also decreases the stability difference between the most stable tautomer III and the less stable tautomer IV, offering an explanation for the apparent involvement of this latter tautomer in H/D exchange experiments.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4][5][6] The flexible use of this building block in the biosynthesis of pyrrole-imidazole alkaloids has recently been suggested to be due to the variable reactivity of 1, acting as a nucleophile in tautomeric forms I and III and as electrophile in tautomeric forms II and IV. Equilibration between the respective tautomeric forms thus stands at the center of a comprehensive biosynthetic scheme proposed by Al-Mourabit et al [1] In order to support the participation of different tautomeric forms of 1 along various biosynthetic pathways, Al-Mourabit et al have recently described the results of theoretical studies suggesting the comparable stability of the four tautomeric forms I-IV of 1 shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[228] 4.7. C-H-Oxidation am N-substituierten Kohlenstoffatom [230] war die Totalsynthese von 490 oder verwandten Verbindungen vorher noch nicht beschrieben worden. Auch wenn die Synthese der Pyrrolimidazol-Alkaloide viele Puzzleteile und interessante Schritte enthält, konzentriert sich dieser Aufsatz auf eine wichtige Reaktion in diesen Synthesen: die C-H-Oxidation an einem Kohlenstoffatom, das ein Stickstoffatom trägt (Schema 96).…”
Section: Metallkatalysierte C-h-halogenierung Und C-h-aminierungunclassified